Efficient hydroxylation of flavonoids by using whole-cell P450 sca-2 biocatalyst in Escherichia coli - Hu, Baodong; Zhao, Xinrui; Zhou, Jingwen; Li, Jianghua; Chen, Jian; Du, Guocheng (Frontiers in Bioengineering and Biotechnology, 2023)
The hydroxylation is an important way to generate the functionalized derivatives of flavonoids. However, the efficient hydroxylation of flavonoids by bacterial P450 enzymes is rarely reported. Here, a bacterial P450 sca-2mut whole-cell biocatalyst with an outstanding 3'-hydroxylation activity for the efficient hydroxylation of a variety of flavonoids was first reported. The whole-cell activity of sca-2mut was enhanced using a novel combination of flavodoxin Fld and flavodoxin reductase Fpr from Escherichia coli. In addition, the double mutant of sca-2mut (R88A/S96A) exhibited an improved hydroxylation performance for flavonoids through the enzymatic engineering. Moreover, the whole-cell activity of sca-2mut (R88A/S96A) was further enhanced by the optimization of whole-cell biocatalytic conditions. Finally, eriodictyol, dihydroquercetin, luteolin, and 7,3',4'-trihydroxyisoflavone, as examples of flavanone, flavanonol, flavone, and isoflavone, were produced by whole-cell biocatalysis using naringenin, dihydrokaempferol, apigenin, and daidzein as the substrates, with the conversion yield of 77%, 66%, 32%, and 75%, respectively. The strategy used in this study provided an effective method for the further hydroxylation of other high value-added compounds.